IMPACT OF SOCIOECONOMIC CONDITIONS AND PARENTAL ENCOURAGEMENT ON ACADEMIC ACHIEVEMENT OF SECONDARY STUDENTS IN COOCHBEHAR (Journal of Informatics Education and Research, 2025)
This study explores the impact of socioeconomic conditions and parental encouragement on the academic achievement of secondary students in Cooch Behar, West Bengal. A sample of 280 Class 10 students from coeducational Bengali-medium schools affiliated with the West Bengal Board of Secondary Education (W.B.B.S.E) was surveyed using a descriptive method. The findings reveal a positive association between higher socioeconomic status and better academic performance. Parental encouragement also emerged as a significant factor, with more excellent support linked to higher achievement. Gender differences were noted, with male students reporting slightly stronger family support and better economic conditions. A strong correlation was found between socioeconomic conditions and parental support, suggesting these factors jointly enhance academic success. The study highlights the critical role of familial and economic factors in shaping educational outcomes, offering valuable insights for policies aimed at improving student achievement in similar socio-economic settings.